Colour discrimination in conservation students: the Farnsworth-Munsell 100– hue test - Bailão, Ana (Ge-conservacion, 2012)
The matching colour in retouching depends on the ability of the observer to differentiate colour. This ability was measured on 28 volunteer conservation students of varying aged using a specific test of colour discrimination – the Farnsworth-Munsell 100-hue test. Fourteen of the subjects were aged between 18-28, six between 29-38, seven between 39-48, and one was over 49 years. The final results are: 50% of subjects showed a wide-ranging ability to differentiate colour: none of them was colour blind; 7% of the students, however, have low ability to discriminate hues but only one was aware of his deficiency. The author aims to reveal the importance of this test for the conservators, using it as a detector to select eligible subjects with high sensibility in colour discrimination, which is an essential predisposition to perform accurate colour matching in retouching.